Difusión del Corn Stunt Spiroplasma del maíz (Spiroplasma kunkelii) y del vector (Dalbulus maidis) en la República Argentina - Giménez Pecci, María de la Paz (2002)
Among the most important diseases that affect the corn crops (Zea mays L.) is “Corn Stunt Spiroplasm” (CSS). It is caused by Spiroplasm kunkelii and transmitted by a cicadelid Dalbulus maidis (De Long & Wolcott, 1923), the only vector known up to the present in Argentina. Corn crop were monitored in 10 provinces of Argentina during 1991/1992, 1994/1995, 1996/2000. This provided information about the growth of this disease since its detection in the year 1990/1991 up to the present in Argentina as well as the distribution of D. maidis, its vector. The detection of the pathogen was performed on plants with symptoms that are characteristic of CSS using the technique of NC-ELISA. The vector was captured by sweeping plants of corn with symptoms. A increase in the areas affected by CSS was shown in the provinces of Jujuy, Salta, Tucumán, Catamarca, Chaco, Corrientes and Santiago del Estero as well as its recent detection in the provinces of Córdoba, San Luis and La Pampa. Based on the 83 places monitored, D. maidis was present in 80 % of the samples and the pathogen was detected in 96%. In the provinces Corrientes, Córdoba, San Luis and La Pampa, D. maidis was not registered.